2018
DOI: 10.1039/c8ja90012d
|View full text |Cite
|
Sign up to set email alerts
|

Atomic spectrometry update: review of advances in atomic spectrometry and related techniques

Abstract: SUMMARY OF CONTENTS This review covers developments in 'Atomic Spectrometry'. It covers atomic emission, absorption, fluorescence and mass spectrometry, but excludes material on speciation and coupled techniques which is included in a separate review. It should be read in conjunctionwith the other related reviews in the series. [1][2][3][4][5][6] Sample introductionThis section covers developments in sample introduction for all instrumental methods. LiquidsLiquid sample introduction relates to methods wherein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 216 publications
0
8
0
Order By: Relevance
“…This latest update adds to that from last year 1 and complements the five other annual Atomic Spectrometry Updates 2,3,4,5,6 . The interest highlighted in the 2018 elemental speciation ASU on the measurement of metal species in biological systems has continued with the publication of a book entitled 'Metallomics: The Science of Biometals,' volume 1055 in the series Advances in Experimental Medicine and Biology 7 .…”
Section: Topical Reviewsmentioning
confidence: 84%
“…This latest update adds to that from last year 1 and complements the five other annual Atomic Spectrometry Updates 2,3,4,5,6 . The interest highlighted in the 2018 elemental speciation ASU on the measurement of metal species in biological systems has continued with the publication of a book entitled 'Metallomics: The Science of Biometals,' volume 1055 in the series Advances in Experimental Medicine and Biology 7 .…”
Section: Topical Reviewsmentioning
confidence: 84%
“…Studies about the effects of experimental factors on the processes of electrothermal atomization are of current interest. 21 One important aspect which needs to be investigated is the type of species formed by the solid-state reaction between PGPs and the refractory elements. Previous studies by several techniques 22–25 have suggested that interactions between the carbon surface and the analyte lead to the formation of carbides and thus affect atomization processes.…”
Section: Introductionmentioning
confidence: 99%
“…These shortcomings for the offline analysis of solid samples require the development of directly on-line analytical methods. Very recently, some new methods to directly analyze solid samples have been reported. , Obviously, laser ablation (LA) sampling dominates the direct analysis of solid samples. Pulsed LA produces an intense burst of energy, which focuses on the surface of solid samples and converts the solid-phase constituents into vapor-phase constituents (vapor and particles) on the nanosecond timescale .…”
Section: Introductionmentioning
confidence: 99%